Determinants of Perinatal Morbidity and Mortality Due to Preterm Deliveries in a Referral Hospital, in Rural India, a Cross Sectional Study - Mahesh Asalkar (New Frontiers in Medicine and Medical Research Vol. 7, 2021)
Preterm birth is the most significant problem in current obstetric practice and according to the World Health Organization is the direct cause accounting for 24% of neonatal deaths. There is scarcity of data on preterm birth in India despite having highest number of births and neonatal deaths in the world. According to the current data, prematurity and associated complications are responsible for 15% of all newborn deaths. Objective of this study was to estimate the Perinatal morbidity and mortality due to preterm deliveries in a referral hospital, in rural India. Cross sectional study design was adopted to estimate the magnitude of preterm morbidity and mortality over 3 years.3843 pregnant mothers delivered in rural referral Medical College, Pune out of which there were 27 cases of twins (24 preterm twins and 3 term twins) and 2 cases of triplets (preterm). After removing the neonates with deadly congenital abnormalities, 476 (12.2%) of the 3874 newborns were preterm. The study looked at 448 mothers (24 preterm twins and 2 preterm triplets) who gave birth to 476 premature newborns, excluding those with lethal congenital abnormalities. Preterm births were found to be responsible for 61.50 percent of perinatal deaths in this study. There were 83 stillbirths and 120 early neonatal deaths out of 476 preterm newborns, resulting in a perinatal mortality rate of 426.4 per thousand preterm births. RDS, septicaemia, IUGR, and birth asphyxia were the leading causes of perinatal morbidity. RDS (18.32 percent), septicemia (22.5 percent), extreme preterm (14.16 percent), and birth asphyxia were all highly linked to infant death (26 percent). This study highlights that reduction in perinatal deaths can be facilitated by increasing awareness for registration of pregnant women for antenatal care. Early registration during pregnancy can certainly help to prevent future consequences of preterm birth babies, still births, and neonatal deaths. Every teaching institute should have at least level 2 neonatal care facilities to make a significant dent in early neonatal deaths.